Efektivitas Ferrofluid dalam Penurunan Parameter Limbah Laundri - Bernadheta Donabella Ega; Novirina Hendrasarie (Fakultas Teknik, 2023)
One of the new applications of ferrofluid, a colloidal compound containing magnetic nanoparticles, is the removal of microplastics from water. Laundry waste has a high concentration of microplastics, but this wastewater contains other substances besides microplastics, such as TSS, COD, surfactants, etc. Therefore, it is necessary to analyze the effectiveness of this method directly from wastewater to determine the total amount. The following is the highest percentage reduction obtained for each parameter: microplastic content of 66.16% is reduced. Then for the TSS parameter, ferrofluid reduces TSS by 70%. As for TDS, the ferrofluid method has the highest percentage reduction of 50.3%. Furthermore, for surfactants or detergents, the highest decrease in ferrofluid was only 10.37%. Lastly, in COD, the biggest decline reached 30%.